Practice of Kangaroo Mother Care: Unveiling Implementation Among Healthcare Providers in Sokoto, North-Western Nigeria - Adamu, Asma'u; Omeneke Isezuo, Khadijat (Al-Athfal: Jurnal Pendidikan Anak, 2024)
Purpose – To assess the proportion of Health Care Providers (HCPs) in Sokoto practicing Kangaroo Mother Care (KMC) in their various health facilities and identify barriers to KMC practice among HCPs in Sokoto. The purpose of this research is to evaluate the extent of KMC adoption and uncover the obstacles that hinder its effective implementation. Design/methods/approach – A cross-sectional descriptive study was conducted among 80 Health Care Providers (HCPs) who attended the World Prematurity Day celebration in 2022. The program was held at the Medical and Health Workers Union office, Tamaje, Sokoto, on December 2, 2022. A structured questionnaire comprising both open and close-ended questions was used. Data obtained were analyzed using SPSS version 25. Findings – The mean age of the HCPs was 32.9±7.6 years, with the majority, 30 (37.5%), having less than five years of working experience. Of the 80 respondents, 41 (51.3%) were nurses, 9 (11.2%) were doctors, and 16 (20.0%) were midwives. Forty-three (53.7%) of the HCPs practiced KMC. The most common barriers to implementing KMC among the HCPs were lack of privacy for the mothers (23, 28.8%), lack of space for the mothers (21, 26.3%), cultural reasons (19, 23.8%), and lack of skills on KMC (16, 20.0%). The factors associated with the practice of KMC were previous training on KMC and working in tertiary hospitals (p<0.05). Research implications/limitations – This research implies that to mitigate barriers to KMC practice in hospitals, HCPs need to be trained to acquire skills for KMC, and rooms for KMC that ensure privacy for mothers should be available in health facilities. Practical implications –By identifying and addressing the barriers to KMC, such as lack of privacy, space, and skills, health facilities can improve the adoption and effectiveness of KMC practices. Originality/value – Kangaroo Mother Care reduces morbidity and mortality in Low Birth Weight (LBW) infants, making it crucial for countries with scarce resources to adopt this practice. Healthcare providers play a vital role in educating, supporting, and assisting mothers to practice KMC in the hospital and continue it at home after discharge. Paper type Research paper